Determinasi Faktor Lingkungan Sosial dan Persepsi Terhadap Keberlanjutan Profesi Petani di Wilayah Agraris Kecamatan Wanasari - Khoerul Anam; M. Erwin Dwi Listiyanto; Khusnul Khotimah; Suci Nur Utami; Zam Zam Kasir (Universitas Veteran Bangun Nusantara, 2026)
This study aims to analyze the influence of perception, factor, social environment, and motivation variables on the interest of the younger generation in continuing the farming profession in Wanasari District. The agricultural sector in this region faces a major challenge in the form of a regeneration crisis due to the massive expansion of manufacturing industrial zones. This quantitative research collected data through structured questionnaires distributed to 97 productiveage respondents (17–30 years old) in Klampok Village using a simple random sampling technique. Data were analyzed using multiple linear regression via the SPSS program. The ttest results indicate that the variables of perception (t = 2.908), social environment (t = 13.031), and motivation (t = 3.968) have a positive and significant partial effect on youth interest. Conversely, the factor variable does not have a significant effect (t = 1.047; Sig. = 0.298). The social environment is proven to be the most dominant determinant in shaping youth career orientation. Simultaneously, all variables have a significant simultaneous effect (F = 135.919; Sig. = 0.000) with an Adjusted R Square value reaching 84.9%. In conclusion, the synergy of strengthening family social environment support and agribusiness modernization is highly crucial to maintaining the sustainable regeneration of the rural agricultural sector.